EQUAL GENDER REPRESENTATION IN EFL INSTRUCTIONAL MATERIALS DURING EMERGENCY REMOTE LEARNING - Hilda Triyaswati; Ive Emaliana (Sanata Dharma University, 2021)
Gender representations in EFL instructional materials can be given less attention amid covid-19 pandemic because there are abundant resources offered in online learning. The current paper aims to investigate a measurement to determine whether males and females are portrayed equally in EFL instructional materials, as proposed in RUU No. 81 A of 2013 the Republic of Indonesia's Ministry of Education and Culture which stated: “The curriculum should be oriented toward the production of good manners and a fair attitude, with a focus on gender equality